2016
DOI: 10.1021/acscatal.6b00714
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Catalysis with Nanoparticles: Bimetallic Alloy Systems and Surface Adsorbates

Abstract: Transition metal nanoparticles are privileged materials in catalysis due to their high specific surface areas and abundance of active catalytic sites. While many of these catalysts are quite useful, we are only beginning to understand the underlying catalytic mechanisms. Opening the "black box" of nanoparticle catalysis is essential to achieve the ultimate goal of catalysis by design. In this Perspective we highlight recent work addressing the topic of controlled catalysis with bimetallic alloy and "designer" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
135
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 121 publications
1
135
0
Order By: Relevance
“…The use of various metal/metal oxide ENPs similar to those found in toners and PEPs, such as iron, manganese, titania, zinc and copper have been known to have enhanced catalytic properties due to the increased reactivity and selectivity of these metallic particles (41,4346). It is also worth noting that other particle formation mechanisms involving ozone, in addition to the nano scale metal and metal oxide particles added and released form the toners during printing, have been proposed in previous studies and may also contribute to this VOC transformation phenomenon taking place and reported in this study [(14, 59).…”
Section: Resultsmentioning
confidence: 99%
“…The use of various metal/metal oxide ENPs similar to those found in toners and PEPs, such as iron, manganese, titania, zinc and copper have been known to have enhanced catalytic properties due to the increased reactivity and selectivity of these metallic particles (41,4346). It is also worth noting that other particle formation mechanisms involving ozone, in addition to the nano scale metal and metal oxide particles added and released form the toners during printing, have been proposed in previous studies and may also contribute to this VOC transformation phenomenon taking place and reported in this study [(14, 59).…”
Section: Resultsmentioning
confidence: 99%
“…Bimetallic nanocatalysts combine the individual properties of their constituents and possess improved stability, catalytic activity, and selectivity. Ni‐based bimetallic NPs have been extensively employed in different coupling reactions, including Sonogashira and Ullmann reactions . In our previous study, it was shown that Fe 3 O 4 @Ni NPs can be employed as a very efficient catalyst in coupling reactions …”
Section: Introductionmentioning
confidence: 99%
“…Ni-based bimetallic NPs have been extensively employed in different coupling reactions, including Sonogashira and Ullmann reactions. [67,68] In our previous study, it was shown that Fe 3 O 4 @Ni NPs can be employed as a very efficient catalyst in coupling reactions. [69,70] Nowadays, considerable attempts are being made for the development of one-pot multi-component reactions to form new C-C bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, protective agents, such as polymers, ligands, and surfactants, are usually required during preparation to obtain stable monodisperse nanocrystals with specific morphologies and structures. For better or worse, protective agents adsorbed on the surface of nanocrystals will extremely affect the catalytic property of the nanocatalyst . Consequently, research on the effect of protective agents upon the catalytic property of nanocrystals is significant for understanding the intrinsic reaction behaviors of reactant molecules over nanocrystal catalysts, and helpful for further design and application of highly efficient catalysts prepared with various nanocrystals as building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid‐phase catalytic reaction is widely employed in the manufacture of synthetic organic chemicals, which is an important topic in nanocatalysis as well . Compared with gas‐phase catalytic reaction and electrocatalytic reaction, the situation in liquid phase is more complex because of the impact of the solvent environment on the nanocrystal surface, adsorbed protective‐agent molecules, and reactants during the reaction process.…”
Section: Introductionmentioning
confidence: 99%